COVID-19 Pandemic: Effect on Medical Education - Islam, Md Tanvirul; Kamal Pasha, AKM Mustafa (Journal of Armed Forces Medical College, Bangladesh, 2021)
Abstract not available JAFMC Bangladesh. Vol 15, No 1 (June) 2020: 1-2